Sektor Informal Sebagai Ketahanan Pangan Dalam Pilar Pertahanan Ekonomi Demokrasi - Rina Nurhayati (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
Small businesses are in the informal sector among the lower layers of society in order to survive. Global economic conditions amid an increasingly competitive force people to think creatively. Create a wide variety of ideas results, fikir power, which is manifested in a real innovative. Emerging creative economy and bloom like mushrooms grown where - where in the form of a small business, is now becoming a phenomenon. The phenomenon that is present as a result of the effort to be able to defend themselves in a hostile economic conditions.This research was conducted through a qualitative method approach with a descriptive case study that describes the informal sector as a pillar of food security in supporting the social economy. Through informal businesses in this global competition, the fact that businesses in the community canteen trader is able to survive in the midst of heavy and hard to face the era of the Asean Economic Community (AEC) by the inclusion of a wide range of formal business sectors on a large scale. Many investors into Indonesia with the ease of getting the facility. In the end, small businesses in the informal sector with a wide range of creative product capable of competing creative ideas continue to be developed along with the ability and willingness to be applied in the work of innovative, to be able to continue to live better. This is the central pillar of food security which occur in supporting community economy competitive.